Interarm Blood Pressure Difference in Young Healthy Adults - Karmacharya, Poonam; Bhattarai, Anshu; Tiwari, Indu (Journal of Nepal Health Research Council, 2023)
Background: Inter-arm difference in blood pressure is the difference in the systolic and the diastolic blood pressure between arms of an individual. According to American heart association, interarm Blood Pressure difference of more than 10 mm of Hg are associated with peripheral vascular disease. The present study aims to determine the magnitude of interarm difference in young healthy individuals and to assess whether family history of hypertension, age, sex and Body mass index is related to higher interarm differenceMethods: A cross-sectional study was carried out among 270 students of Manipal College of Medical Sciences, Pokhara, Nepal. Blood pressure was measured in both the arms using a mercury sphygmomanometer. (Elko 300) Statistical analysis was done using paired t test, chi-square and Pearson’s correlation test using SPSS 23. Results: The absolute mean Inter-arm difference for systolic blood pressure was 11.03±0.67mm Hg and for diastolic blood pressure was 6.020 ±0.21 mm Hg. There is significant inter-arm difference for systolic blood pressure and diastolic blood pressure (p<0.001). Inter-arm systolic blood pressure difference was significantly associated with family history of hypertension, age and Body Mass Index (p<0.001) Meanwhile, there was no statistically significant association of sex, family history of hypertension, age and Body Mass Index with inter-arm difference for diastolic blood pressure.Conclusions: Significant inter-arm systolic and diastolic blood pressure differences was found in the young, healthy population. Positive correlation of increased Inter-arm difference in Blood Pressure with family history of hypertension was confirmed. This emphasizes the importance of measuring blood pressure in both arms to be a routine practice as we aim for early diagnosis and prompt treatment of hypertensive disorders.Keywords: Blood pressure; healthy adults; interarm difference